Evaluasi Perkembangan Fintech Syariah Di Indonesia: Studi Pada Aspek Regulasi, Permodalan Dan Literasi Keuangan - Hidayat, Agus; Sururi, Miftahus (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2023)
This research is a comprehensive evaluation of the development of Shariahcompliant Financial Technology (Fintech) in Indonesia, focusing on the aspects of regulation, capitalization, and financial literacy. In the face of the rapid growth of the Shariah Fintech sector and the complexity of the challenges it faces, this research aims to provide an in-depth understanding of key factors influencing the industry's development. The research methodology involves qualitative analysis with a case study approach, encompassing the selection of Shariah Fintech entities, interviews with industry representatives and stakeholders, as well as an examination of regulations and related literature. The findings of this research offer a comprehensive overview of the regulatory landscape, capitalization conditions, and the level of financial literacy within the Shariah Fintech ecosystem. The research findings indicate that minimal regulations, capital constraints, and varying levels of financial literacy significantly impact the development of Shariah Fintech in Indonesia. Recommendations resulting from this research include regulatory reforms to create a supportive environment, facilitation of capitalization, strengthening financial literacy, and international collaboration to promote inclusive and sustainable growth of the Shariah Fintech sector in the future.